Pengaruh Konseling Rational Emotive Behavior Therapy (REBT) Untuk Meningkatkan Resiliensi Siswa Korban Bullying Di SMPN XI Mataram - Farida Herna Astuti; Dewi Rayani; Ni Made Sulastri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Bullying cases in schools have not been resolved optimally. This is very concerning and disturbing for those in the world of education because bullying behavior can have an impact on student behavior in the form of greater aggression in the future. In addition, it can also cause psychological disorders in the form of depression for victims. Providing effective intervention for perpetrators of bullying must be adjusted to the emotional condition of the perpetrator as well as the victim. Thus, one of the right approaches is to provide rational emotive behavior therapy (REBT). The basic assumption of the REBT approach is that it can improve the resilience of students who are victims of bullying to be better. This is proven after REBT counseling, students who are victims of bullying can still adapt to difficult situations and can carry out activities at school.